Miguel Benasayag, "Fonctionner ou exister?" - Marsiglia, Stefano (Filosofia, 2020)
With this book Benasayag does not claim to establish an ‘ontological’ separation between existence and function, but would rather return to that complex unity between the two dimensions of life. Today, we see an indistinctness between function and existence and this is seen in the elderly who are considered ‘old’. To be elderly means, according to Benasayag, determining non-possibilities, that is to say limits that protect, while technology makes us believe that everything is possible. So that every limit must be banished arriving even to, as the merchants of transhumanism do, “considerare la morte come un funzionamento fisiologico che si potrebbe cambiare” (p. 42 [to consider death as a physiological function that could be changed]). We also look almost with horror at our fragilities with the aim of adhering as much as possible to the fluidity and flexibility required. Everything is reduced to the linear time marked by the clock and we are obsessed with gaining time. This book wants to be an invitation to participate in a life that fully manifests itself in every situation, without hiding behind some labels that tell us nothing about who we really are. And to do that you need courage. Because it is only in this way that we can dare to exist and fell fully alive.